1995
DOI: 10.1143/jjap.34.l760
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopic Observation of AlN/α-Al2O3 Heteroepitaxial Interface with Initial-Nitriding AlN Layer

Abstract: A pulse programmer is described which generates a wide range of pulse sequences for use with nuclear resonance equipment. The use of chfos integrated circuits makes the unit extremely small and cheap and allows the incorporation of a very simple power supply.Abstract An automatic microtome has been designed for cutting 400 pm snippets of wool and other fibres very uniformly and with square ends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 8 publications
4
13
0
1
Order By: Relevance
“…In the case of (OO.1)A1N grown on (OO•l) sapphire substrate, the EADM shows smallest value between eight time N-N distances of epilayer and nine times 0-0 distances of the substrate from the growth model. This model has confirmed by transmission electron microscopic observation ofthe cross-sections reported by Masu et al(1995). 9 It was revealed that strain of epilayer has reduced by edge-type dislocations and EADM would suggest and appear the possibility of the epitaxial growth.…”
Section: Introductionsupporting
confidence: 65%
“…In the case of (OO.1)A1N grown on (OO•l) sapphire substrate, the EADM shows smallest value between eight time N-N distances of epilayer and nine times 0-0 distances of the substrate from the growth model. This model has confirmed by transmission electron microscopic observation ofthe cross-sections reported by Masu et al(1995). 9 It was revealed that strain of epilayer has reduced by edge-type dislocations and EADM would suggest and appear the possibility of the epitaxial growth.…”
Section: Introductionsupporting
confidence: 65%
“…Over the years, GaN with different orientations have been shown practically by all growth techniques, HVPE [7,15], metalorganic vapor phase epitaxy (MOVPE) [9,10,14,[17][18][19][22][23][24][25][26], MBE [8,11,12,20,21,27]. For more than 20 years, all the publications consistently reported that the nitride growth in directions different from the [0001] one is more difficult.…”
Section: The Initial Results On Nitrides Grown With Off-c-axis Orientmentioning
confidence: 99%
“…Although the first realizations of AlN with nonpolar (1120) surface [8,22,23,25,26] and (1100) surface [24] were reported before 2000, a systematic study of nonpolar AlN-based materials, aiming at the development of AlN/AlGaN heterostructures for device applications started at Kyoto University in 2002 [32,33]. By using both 6H and 4H-SiC substrates, both a-and m-plane structures have been brought into the focus of further research.…”
Section: The Beginning Of the Nonpolar Nitridesmentioning
confidence: 99%
“…[4][5][6] High quality GaN can also be obtained by nitridation of a substrate with ammonia before the film growth. [7][8][9][10] In both cases, there seems to be optimum growing conditions where two-dimensional (2-D) nucleation and lateral growth is enhanced for the best crystal quality. The process window to get the best film is generally reported to be a function of temperature and time for a given deposition system.…”
Section: Introductionmentioning
confidence: 99%